The Effect of Sharia Financial Literacy, Risk Perception and Return Expectation on Sharia Stock Investment Decision Making in Islamic Business Perspective (Study on Generation Z in Bandar Lampung who Actively Invest) - Maulana, Bintang; Purnamasari, Femei; Susanto, Is (CV. Civiliza Publishing, 2025)
This study aims to measure and analyze the effect of Islamic financial literacy, risk perception, and return expectations on investment decision-making Islamic stocks among Generation Z in Bandar Lampung. The approach used is quantitative, with data collection through questionnaires distributed to 100 respondents selected using purposive sampling technique. Data analysis technique used is multiple linear regression with the help of SPSS software version 26. The results of the study partially indicate that Sharia financial literacy has a positive and significant influence on investment decisions, which means that the higher the understanding of Islamic financial principles, the higher the tendency to invest in Sharia. Risk perception also has a positive and significant effect, which shows that respondents can manage risk wisely and are not easily hindered by it in making investment decisions. Return expectations show a positive and significant influence, where the greater the expectation of investment returns, the stronger the intention to invest. Simultaneously, these three variables contributed 77.7% to changes in investment decisions. These findings reinforce the understanding that Generation Z has a rational mindset and spiritual values in assessing Islamic stock investment opportunities.